Motivational and Affective Factors Underlying Consumer Dropout and Transactional Success in eCommerce: An Overview - Bell, Lynne; McCloy, Rachel; Butler, Laurie; Vogt, Julia (Frontiers in Psychology, 2020)
It is estimated that more than half of all online transactions are abandoned before completion. This paper investigates the psychological factors that influence online shopping behavior, with a view to improving transactional success rates. Through a critical review of the literature, we identify a range of factors which predict abandonment of online shopping, highlighting affective and motivational dimensions in addition to processing style and characteristics of the consumer, device, and product. We conclude that online purchasing and payment systems that boost consumers’ motivation to buy and prevent or attenuate negative affective states will demonstrate the greatest rates of transactional success. However, with rapid advancement in technology, continued research is needed to fully understand the potential impact on future online purchasing behavior.